Kadrowanie egzystencji: Klara Nowakowska - Stusek, Marta (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The article discusses the works of Klara Nowakowska, including all published volumes of the poet. Interpretations of specific works, as well as overall analyses present poems of Nowakowska as cropped images which in the imperfect way are reflecting reality. The article’s author stress the meaning of the specific variety of the short poetic form used by poet. Parallel, analysis includes the poetic record of experiencing the place.